Electrochromic and electrofluorochromic behavior of novel polyurea bearing oligoaniline and triphenylamine units. (3rd January 2018) - Yan, Ying; Sun, Ningwei; Jia, Xiaoteng; Liu, Xincai; Wang, Ce; Chao, Danming
Abstract: Electroactive materials have gained increasing attention for their intelligent applications. In this work, we report the design and synthesis of a novel electrochromic and electrofluorochromic dual-switching polyurea bearing oligoaniline and fluorescent triphenylamine units (PUOT). Cyclic voltammogram of PUOT exhibits two reversible redox couples at 0.96 V/0.73 V and 1.36 V/1.11 V (vs. Ag/AgCl reference electrode), ascribed to the redox transformation of oligoaniline and triphenylamine groups, respectively. In this wide potential window (0–1.6 V), the PUOT film reveals a unique multistage regulated electrochromic behavior with maximal transmittance contrast value of 38% switching from 0.0 V to 1.0 V, and partial transmittance contrast value of 14% (0–1.6 V) and 24% (1.0–1.6 V). Furthermore, its electrofluorochromic behavior has also been disclosed at the potential range of 0–1.0 V, which demonstrates that the oligoaniline groups should be served as electroactive units in this electrofluorochromic system. Our research not only presents a deep understanding of the optical-electrical modulation mechanism but also paves the way for their future applications. Graphical abstract: We report the synthesis of a novel polyurea, containing oligoaniline and fluorescent triphenylamine groups. The polyurea exhibits unique multistage regulated electrochromic feature and attractive electrofluorochromic behavior. Image 1 Highlights: A novel polyurea bearing two kinds of electrochromic units was reported. The polyurea exhibits unique multistage regulated electrochromic feature. An interesting electrofluorochromic behavior has been disclosed and studied.